The Effects of Right Offering Announcements on Returns of Shares of Deposit Banks Traded in İstanbul Stock-Exchange - Kendirli, Selcuk; Elmali, Muhammet Emin (Journal of Economic Development, Environment and People, 2016)
In this study, the impacts of right offerings announcements on the returns of shares are analysed. Right offerings means to have the rigth of receiving new shares in proportion to shares on hand when the corporation issues new shares for outsourcing capital increase. In this study, before and after the right issue announcements, the abnormal returns (AR) of shares of the banks in Istanbul Exchange Market-100 calculated and the return changes are analysed.